A Preliminary Discussion on the Characteristics of Thought and Faith Among Early Qing Confucian Christians - XIAO, Qinghe (Journal of Research for Christianity in China (JRCC), 2025)
Confucian Christians in the Early Qing Dynasty belonged to the third generation of believers during the Ming and Qing periods. Their thought and faith shared certain similarities with the first and second generations, yet also exhibited distinct differences. This paper provides an overview and discussion of the thought and faith of early Qing Confucian Christians from a macro perspective, aiming to clarify the overall profile of this group.
Keywords: Early Qing Dynasty, Confucian Christians, Thought, Faith